Left Behind or Unseen Potential? A SWOT and 7Ps of Marketing-Based Evaluation of Biliran Island’s Tourism Development : A Strategic Evaluation of Biliran Island’s Tourism Using SWOT and Marketing Mix Frameworks - Carreon, Junard (Politeknik Pariwisata NHI Bandung, 2026)
This study examined the perceptions of tourism development in Biliran Island through the lens of the 7Ps of marketing, comparing insights from local residents and respondents outside the province. Utilizing the Wilcoxon Signed-Rank Test, a statistically significant difference was found between the two groups, with outsiders holding more favorable views than locals (z = -4.106, p < .001). Further non-parametric analyses, including Mann-Whitney U and Kruskal-Wallis tests, explored the influence of demographic variables such as sex, age, education, occupation, income, frequency of visit, and purpose of travel. While some variables showed no significant influence, notable differences emerged in perceptions based on salary, purpose of visit, and region, indicating that socio-economic status and motivation for travel affect how tourism development is evaluated. The findings suggest that Biliran Island is not entirely left behind but holds unseen potential that remains underappreciated by its own residents. Outsiders perceive the island more optimistically, highlighting the need for inclusive, community-based tourism development that bridges the perception gap. Strategic investments in infrastructure, stakeholder collaboration, and community empowerment are recommended to transform Biliran into a recognized, sustainable tourism destination.